2013
DOI: 10.4103/0019-5545.120546
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression and lesion location: A hospital based cross-sectional study

Abstract: Background:Depression is a common neuro-psychiatric consequence of stroke, affecting approximately 40% of the patients. Many studies show that in addition to the psychosocial stress, neurobiological factors such as site of infarct and brain atrophy may also be related to Post Stroke Depression (PSD). There are conflicting results in this area of research and paucity of such data in Indian literature. Thus the aim of this study is to weigh the importance of lesion location in PSD.Materials and Methods:Sixty two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
6
40
0
1
Order By: Relevance
“…According to the criteria outlined above after screening based on their abstracts, we initially excluded 3,758 citations. After we screened their full texts, we found that 31 original reports included categorical data on both depression and gender and were included in the meta-analysis (Folstein, Maiberger, & McHugh, 1977;Andersen, Vestergaard, Ingemann-Nielsen, & Lauritzen, 1995;Herrmann, Bartels, Schumacher, & Wallesch, 1995;Bjerg Bendsen, Bjerg Bendsen, Lauritzen, Vilmar, & Bech, 1997;Kase et al, 1998;Gainotti, Antonucci, Marra, & Paolucci, 2001;Singh et al, 2000;Desmond et al, 2003;Hsieh & Kao, 2005;Nys et al, 2005;Tang et al, 2005;Glodzik-Sobanska et al, 2006;Caeiro, Ferro, Santos, & Figueira, 2006;Brodaty, Withall, Altendorf, & Sachdev, 2007;Fuentes, Ortiz, Sanjose, Frank, & Diez-Tejedor, 2009;Nidhinandana et al, 2010;Nishiyama et al, 2010;Tennen et al, 2011;Shi et al, 2015;Choi-Kwon et al, 2012;Zhang, Pan, Wang, & Zhao, 2013;Rajashekaran, Pai, Thunga, & Unnikrishnan, 2013;Angeleri et al, 1997;Finklestein et al, 1982;Grasso et al, 1994;Ng, Chan, & Straughan, 1995;Sun et al, 2014;Jiang, Lin, & Li, 2014;Saxena & Suman, 2015;Wei et al, 2016;Metoki et al, 2016). The study characteristics and demographics are provided in Table 1.…”
Section: Characteristics For Studies Includedmentioning
confidence: 99%
“…According to the criteria outlined above after screening based on their abstracts, we initially excluded 3,758 citations. After we screened their full texts, we found that 31 original reports included categorical data on both depression and gender and were included in the meta-analysis (Folstein, Maiberger, & McHugh, 1977;Andersen, Vestergaard, Ingemann-Nielsen, & Lauritzen, 1995;Herrmann, Bartels, Schumacher, & Wallesch, 1995;Bjerg Bendsen, Bjerg Bendsen, Lauritzen, Vilmar, & Bech, 1997;Kase et al, 1998;Gainotti, Antonucci, Marra, & Paolucci, 2001;Singh et al, 2000;Desmond et al, 2003;Hsieh & Kao, 2005;Nys et al, 2005;Tang et al, 2005;Glodzik-Sobanska et al, 2006;Caeiro, Ferro, Santos, & Figueira, 2006;Brodaty, Withall, Altendorf, & Sachdev, 2007;Fuentes, Ortiz, Sanjose, Frank, & Diez-Tejedor, 2009;Nidhinandana et al, 2010;Nishiyama et al, 2010;Tennen et al, 2011;Shi et al, 2015;Choi-Kwon et al, 2012;Zhang, Pan, Wang, & Zhao, 2013;Rajashekaran, Pai, Thunga, & Unnikrishnan, 2013;Angeleri et al, 1997;Finklestein et al, 1982;Grasso et al, 1994;Ng, Chan, & Straughan, 1995;Sun et al, 2014;Jiang, Lin, & Li, 2014;Saxena & Suman, 2015;Wei et al, 2016;Metoki et al, 2016). The study characteristics and demographics are provided in Table 1.…”
Section: Characteristics For Studies Includedmentioning
confidence: 99%
“…Besides generating a negative impact on functional rehabilitation, it represents one of the most prominent causes to increase mortality in this population (1) . Depression has been detected in between 20 and 60% of stroke patients, this rate ranging in accordance with the evaluation criteria established (by means of scales or semi-structured interviews, for instance), as well as to the population investigated (such as ischemic and/or hemorrhagic, chronic and/or acute stroke) (2) and lesion location.…”
Section: Introductionmentioning
confidence: 99%
“…Multiprofessional rehabilitation is often necessary among those survivors as most of them have significant disabilities. Post‐stroke depression (PSD) is a common neuropsychiatric complication and has been reported to occur more often in the young stroke patients, females, and those with more severe symptoms . Depressed mood has been reported to be present in 20% of ICH survivors .…”
mentioning
confidence: 99%